Effect of New Pd(Ii)-Aroylthiourea Complex on Pancreatic Cancer Cells - Echeverria-Morgado, J (Elsevier B.V., 2021)
A Pd(II) complex bearing N-((2,6-diisopropylphenyl)carbamothioyl)-4-methylbenzamide (C1) has been prepared and characterized by various spectroscopic studies, and elemental analysis. Crystal structure of the ligand (L1) and C1 was confirmed by single crystal X-ray diffraction tool, which revealed the square planar (trans) geometry for C1. Binding ability of C1 with biomolecules (CT DNA and BSA) was studied by absorption and fluorescence methods, which showed good binding efficiency of the complex with targeted biomolecules. The intercalation binding mode was inferred for the Pd(II) complex with DNA. The stability of C1 was studied by NMR spectroscopy which indicated that C1 was stable up to 72 h. Further, L1 and C1 have been evaluated for their anticancer property against four pancreatic cancer (AsPC-1, BxPC-3, PANC-1 and MIA PaCa-2) and one normal (Vero) cell lines. C1 showed potential anticancer activity towards MIA PaCa-2 with an IC50 value of 15.27 µM. Positively, L1 and C1 displayed less toxicity (>100 µM) towards Vero normal cells. © 2021 Elsevier B.V.